1988
DOI: 10.1111/j.1469-8749.1988.tb04773.x
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Ultrasound Diagnosis of Pathologically Verified Lesions in the Brains of Very Preterm Infants

Abstract: SUMMARY Abnormalities detected by a mechanical sector scanner were compared ‘blind’ with autopsy findings in the brains of 56 infants born at less than 33 weeks gestation. Intraventricular haemorrhage was found in 53 of 112 hemispheres and had been accurately diagnosed by ultrasound (sensitivity 91 per cent; specificity 81 per cent). Isolated germinal layer haemorrhage was less successfully identified (sensitivity 61 per cent; specificity 78 per cent); false‐positive diagnoses were partly due to difficulty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(32 citation statements)
references
References 33 publications
1
28
0
3
Order By: Relevance
“…Although MRI is the optimal imaging modality to define WMI in preterm survivors [115][116][117][118], the histopathological features of MRI signal abnormalities have been mostly defined for WMI where periventricular leukomalacia predominates [64,[119][120][121][122][123]. With the pronounced shift to milder forms of human WMI defined by quantitative and diffusionweighted MRI, there is a need to define the cellular features of these lesions.…”
Section: Role Of High-field Mri To Define Pathological Features Of Wmimentioning
confidence: 99%
“…Although MRI is the optimal imaging modality to define WMI in preterm survivors [115][116][117][118], the histopathological features of MRI signal abnormalities have been mostly defined for WMI where periventricular leukomalacia predominates [64,[119][120][121][122][123]. With the pronounced shift to milder forms of human WMI defined by quantitative and diffusionweighted MRI, there is a need to define the cellular features of these lesions.…”
Section: Role Of High-field Mri To Define Pathological Features Of Wmimentioning
confidence: 99%
“…Entretanto, a presença destes indicadores não assegura a confirmação do prejuízo para o desenvolvimento [17][18][19][20] .…”
Section: Introductionunclassified
“…Because changes on MRI correspond closely to histopathologic changes found on postmortem examination, [45][46][47][48][49] MRI can be applied in vivo to better anticipate the neurodevelopmental outcome after neonatal brain injury. A number of investigators have found that the severity and pattern of brain injury in the term newborns after a hypoxic-ischemic insult are strongly predictive of neurodevelopmental outcomes.…”
Section: Mri As An Early Outcome Measurementioning
confidence: 99%